The application of natural zeolite to cement concrete intended for communications surfaces - Linek, Małgorzata; Żebrowski, Wojciech; Wolka, Paweł (E3S web of conferences, 2018)
The article presents the application of a cement substitute in the form of natural zeolite to cement concrete. The reference mix design intended for communications surfaces and a mix of modified composition taking into consideration zeolite content were prepared. The basic parameters of concrete mix components were specified, including basalt aggregate, cement and zeolite. The influence of the applied zeolite of a grain-size distribution up to 50μm on the obtained parameters of concrete mix and hardened concrete was determined. It was observed that the applied zeolite contributes to the modification of the internal structure of concrete composite and consequently to the increase of the mechanical and physical parameters of hardened concrete tested within diversified standard periods of time. Due to the fact that the resistance of concrete to cyclic freezing and thawing is the determinant of concrete durability, in the case of pavement structure, hardened concretes were subject to a frost resistance assessment. The influence of zeolite content on both internal and external frost resistance of hardened concrete was specified. SEM observations of the internal structure of concretes exposed to the influence of freezingthawing cycles proved the advantageous changes of zeolite occurrence in concrete mix. A reduction of cement quantity and its replacement thereof with the suggested zeolite allows obtaining a pavement quality concrete of a more favourable internal micro structure and distinguished by higher parameters.